دراسة الالتحام الجزيئي والتنبؤ لمركبات الزيت لنبات الأساسي - بن علي الخنساء; ثامر الزهرة (جامعة الوادي - university of eloued, 2024)
To contribute to the development of more potent inhibitors for certain enzymes such as Human Abl kinase, Staphylococcus aureus tyrosyl-tRNA synthetase, Acetylcholinesterase, Desulfo-Xanthine Oxidase, and penicillin-binding protein 3, for the treatment of cancer, Alzheimer's disease, bacterial infections, and oxidation disorders, we employed in silico methods by studying the molecular docking of these enzymes with key compounds from the essential oil of Anthemis stiparum (Camphor, Germacrene D, T-cadinol, Spathulenol and salicylate Isoamyl) using Autodock software. Subsequently, the ADMET properties of the compounds were evaluated using the Swiss ADME and Protox websites to assess the physical, chemical, and pharmacokinetic properties of these compounds. The results obtained from molecular docking and ADMET properties examination revealed that the compound Germacrene D has inhibitory potential against Human Abl kinase with a binding energy of -7.91 kcal/mol, Desulfo-Xanthine Oxidase with a binding energy of - 7.38 kcal/mol, and AChE with a binding energy of -8.7 kcal/mol, indicating potential for treating cancer, oxidative disorders, and Alzheimer's disease, respectively. Additionally, the results showed that the compounds T-cadinol and Spathulenol could be inhibitors for penicillin-binding protein 3 and Staphylococcus aureus tyrosyl-tRNA synthetase, respectively, for treating bacterial infections. These results suggest the potential exploitation of these compounds (Germacrene D, Tcadinol, and Spathulenol) as promising inhibitors for these enzymes to treat cancer, Alzheimer's disease, oxidative disorders, and bacterial infections. Further in vitro and in vivo studies and chemical structure modifications are recommended.
التنوع البيئي وفيزيولوجيا النبات
Keywords: Molecular docking; Anthemis stiparum; essential oil; Autodock software; In silico; ADMET